Fabrication and characterization of advanced transparent ceramics - Chua, Joshua Jie Heng (Nanyang Technological University, 2022)
The properties of transparent polycrystalline ceramics make them ideal for solid-state lasers applications. These properties include higher thermal conductivity and lower thermal expansion. To be able to effectively fabricate a transparent ceramic with excellent transmittance, light scattering factors needs to be resolved. In this experiment, transparent yttria ceramics were fabricated successfully without using sintering aids, via vacuum sintering under different temperatures (1500°C,1525°C,1550°C), followed by hot isostatic pressing (HIP) treatment for co-precipitated yttria powders. Fabricated yttria samples would then undergo characterization techniques such as scanning electron microscopy (SEM), ultraviolet-visible (UV-Vis) spectroscopy, and the buoyancy technique, to analyze the morphology, transmittance, and density respectively. By vacuum sintering at 1525°C for 14h followed by HIP treatment for 1480°C for 3h, a fully dense transparent yttria ceramic with the highest transparency was obtained. The ceramic had a microstructure with fine grains that had an average grain size of 1.054μm. Additionally, in-line transmittance for transparent yttria ceramic reached 80.14% at 1100nm (1mm thickness).